Determination of the parameters of technological schemes of ferrites production with a computer system - Shkurnikov, Eugene Viktorovich (Eastern-European Journal of Enterprise Technologies, 2013)
The article describes a computer system for the removal of the magnetic characteristics. It describes a structural scheme of the computer system for the removal of the magnetic characteristics, which consists of the following software modules: the measuring module, the module of determination of the parameters of mathematical models, the module of transformation of parameters of mathematical models, the module of communication with DBMS, the module of determination of the parameters of technological schemes of production of ferrites. The method of determination of the parameters of technological schemes of production of ferrites was considered. The method is based on a comparison of the parameters of technological schemes of production of ferrites with the parameters of the mathematical model of Giles - Atterton. The comparison is made using the group method of data handling. The group method of data handling (GMDH) relates to a family of inductive algorithms for mathematical modeling of multiparametric data. The method is based on the recursive selective selection of models, on the basis of which more complex models can be built. The modeling accuracy at each further step of recursion increases due to the complication of models.